Detection of Chlamydia species, including those with zoonotic potential, in domestic and wild animals in Costa Rica - Solórzano-Morales, Antony (2026)
Species of the genus Chlamydia are intracellular Gram-negative bacteria that infect a wide range of animals (birds, reptiles, amphibians, and mammals, including humans), and cause a broad variety of diseases. The country’s extensive biological diversity provides suitable niches for the development of Chlamydia transmission cycles, which pose a threat to animal and human health. This research aimed to detect and characterize Chlamydia species in domestic and wild animals in Costa Rica. A total of 333 swabs or tissue samples were collected from animals without clinical signs (299) and with clinical signs (34), which were analyzed by different molecular techniques (real-time and endpoint polymerase chain reaction and sequencing). Of the total samples analyzed, 59 (17.7%) were positive for Chlamydia spp., detected primarily in animals with respiratory disease (50% of cases), and also in animals without clinical signs (14% of cases). In birds, 13.9% (28/201) of the samples were positive; in mammals, 25.9% (21/81); and in reptiles, 19.6% (10/51). The most frequently diagnosed species was Chlamydia psittaci genotype A (22/59.39%), detected for the first time in a cat (Felis catus), a canary (Serinus canaria), a cockatiel (Nymphicus hollandicus), a parrot (Amazona autumnalis), and a green heron (Butorides virescens), thus increasing the range of hosts reported in the country. Chlamydia pneumoniae was reported for the first time in seven snakes (Boa constrictor) and Chlamydia suis in pigs (Sus scrofa domesticus); these findings represent the first reports in Central America and Latin America, respectively. Finally, C. psittaci was detected in a human pharyngeal swab. This data confirms the presence of various species of Chlamydia with zoonotic potential in a wide variety of domestic and wild animals that coexist with humans. Given the risk posed by Chlamydia spp. to public health, it is recommended that biosecurity measures be implemented in establishments that exhibit or sell animals, and that Chlamydia spp. be ruled out in animals and humans with respiratory diseases. It is important to raise awareness an